Do espaço expositivo à mediação em arte e tecnologia: estudo de caso do FACTORS - Quaiatto, Rittieli D’Avila (2019)
This dissertation is in the field of History, Theory and Criticism of Art and aims to present pertinent questions to the relation between expography and mediation in exhibitions of Digital Art and Technology. In order to do so, it is based on the case study of the 4th edition of the Festival of Art, Science and Technology (FACTORS), held in 2017. Considering the technological appropriation adopted by artists and researchers, it is noticed that the productions developed extrapolate the traditional models of exhibition, affect the relation work and exhibition space, as well as the interaction of the public with the exhibition. Through participation and interactivity, the works / projects move the public from the contemplative posture and invite them to experience exposure using others senses beyond sight. From the verification of the elements that configure, constitute, characterize and assist in communication with the public, this dissertation contributes to thinking and discussing the approaches used in Digital Art and Technology exhibitions.